Hubungan Disiplin Dan Motivasi Kerja Dengan Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Way Kanan - Nuria Erisna (Jurnal Manajemen dan Bisnis, 2012)
Problems faced by the Department of Education of Way Kanan District is still not yet optimal employee performance. Many factors could cause the performance of employees such as work discipline and work motivation. The purpose of this study was to determine the relationship between discipline and work motivation with employee performance at the Departement of Education of Way Kanan District. This study uses primary data obtained through observation, interviews and distributing questionnaires to a sample of 48 employees, as well as secondary data were sourced from the literature and document. Analysis tool used is the analysis of the correlation coefficient and the coefficient of determination. From the calculations, the correlation coefficient with the work discipline of employee performance is 0.619, meaning there is a strong and positive relationship between the discipline of working with performance. Correlation coefficient with the motivation of employee performance is 0.318 means there is a relationship between work motivation and performance of employees with a weak category. Correlation coefficient of work discipline and work motivation with the employees performance is 0.639, meaning there is a strong relationship between labor discipline and work motivation with employee performance. The determination coefficient of the relationship between the discipline and work motivation with employee performance is 0.408. It means, that the contribution of work discipline and work motivation with employee performance by 40.8%, and the remaining 59.2% were related to other variables that were not analyzed. Thus, it can be concluded that the work discipline has a stronger relationship with the employees performance compared with the work motivation, but the discipline all together have strong relationship with the employee performance at at the Department of Education of Way Kanan District.Masalah yang dihadapi oleh Kantor Dinas Pendidikan Kabupaten Way Kanan adalah masih belum optimalnya kinerja pegawai. Banyak faktor yang dapat menyebabkan rendanya kinerja pegawai diantaranya adalah disiplin kerja dan motivasi kerja. Tujuan penelitian ini adalah untuk mengetahui hubungan antara disiplin dan motivasi kerja dengan kinerja pegawai pada Kantor Dinas Pendidikan Kabupaten Way Kanan. Penelitian ini menggunakan data primer yang diperoleh melalui observasi, wawancara dan menyebarkan kuisioner kepada 48 orang pegawai sebagai sampel, serta data sekunder yang bersumber dari literatur dan dokumen. Alat analisis yang digunakan adalah analisis koefisien korelasi dan koefisien determinasi. Dari hasil perhitungan diperoleh nilai koefisien korelasi disiplin kerja dengan kinerja pegawai adalah 0,619, berarti terdapat hubungan yang kuat dan positif antara disiplin kerja dengan kinerja. Koefisien korelasi motivasi kerja dengan kinerja pegawai adalah 0,318 berarti terdapat hubungan antara motivasi kerja dan kinerja pegawai dengan katagori yang lemah. Koefisien korelasi variabel disiplin kerja dan motivasi kerja dengan kinerja pegawai adalah 0,639, berarti terdapat hubungan yang kuat antara disiplin kerja dan motivasi kerja dengan kinerja pegawai. Koefisien diterminasi hubungan disiplin dan motivasi kerja dengan kinerja pegawai adalah 0,408. Ini berarti, sumbangan disiplin kerja dan motivasi kerja terhadap kinerja pegawai sebesar 40,8%, dan sisanya sebesar 59,2% berhubungan dengan variabel lain yang tidak dianalisis. Jadi, dapat disimpulkan bahwa disiplin kerja mempunyai hubungan yang lebih kuat dengan kinerja pegawai dibandingkan dengan motivasi kerja, namun secara bersama-sama disiplin dan motivasi kerja mempunyai hubungan yang kuat dengan kinerja pegawai pada Kantor Dinas Pendidikan Kabupaten Way Kanan.